Earnest Hemingway: Sketches Of Life And Works - El Tayeb El Mikashfi, Lubab (Gezira Journal of Educational Sciences and Humanities; مجلد 2 عدد 1 (2005), 2021)
The purpose of this paper is to bring to light the essence of Hemingway's literary achievements for the benefit of the audience; who are concerned with English literature in general and American literature in particular. Investigating Hemingway's life and works reveals his invaluable contribution to English literature in USA and the world-over. His variety of themes related to the period between the two world wars and the simple journalistic style he adopted speak for his mastery of the art of modern narration